Inside the mixed marriage: accounts of changing attitudes, patterns, and perceptions of cross - cultural and interracial marriages - Johnson, Walton; Warren, Michael (New York: University Press of America, 1994)
Contents: Defining and exploring the mixed relationship. Adjusting to racial and cultural pluralism. Becoming a minority throught the study abroad experinece. Immersion in a new culture: living and working abroad
Includes bibliographical references and index
Keywords: Tipos de matrimonios - Matrimonio